Návrh na zdanění příjmů legislativně neošetřeného podnikání v ČR - Kříž, Martin (Vysoké učení technické v Brně. Fakulta podnikatelská, 2013)
Bakalářská práce obsahuje dvě části, teoretickou a praktickou. V teoretické části se práce zabývá stručně historií prostituce, jejím vývojem jak v evropském měřítku, tak i na území dnešní České republiky a také současným stavem právně-daňové úpravy prostituce u nás. Praktická část práce je zaměřena na srovnání dané problematiky s jinými evropskými zeměmi, současně navrhuje, jak by mohla v budoucnu nová úprava vypadat či jak by měla být ta stará zdokonalena.

The Bachelor thesis contains two parts, the theoretical part and the practical part. In the theoretical part of thesis is deal with brief history of prostitution, it’s developement as in europian measure so as in the territory of present land of Czech Republic, also deal with current situation of legally-taxation treatment. The practical part of thesis is focus on comparation of mention threatment with another europian countries and at the same time suggest how the new threatment can look like or how the old one might be innovated.
The Proposal of Taxation Incomes Legislation Nonnursed Enterprise in the Czech Republic
Keywords: Prostituce; legalizace; zákon; zdanění; příjmy; srovnání; návrh; Prostitution; legalization; law; taxation; incomes; compared; proposal